2020
DOI: 10.1021/acs.est.9b06981
|View full text |Cite
|
Sign up to set email alerts
|

Tying up Loose Ends of Microplastic Pollution in the Arctic: Distribution from the Sea Surface through the Water Column to Deep-Sea Sediments at the HAUSGARTEN Observatory

Abstract: Recent studies have shown that despite its remoteness, the Arctic region harbors some of the highest microplastic (MP) concentrations worldwide. Here, we present the results of a sampling campaign to assess the vertical distribution of MP particles (>11 μm) at five stations of the HAUSGARTEN observatory. Water column samples were taken with large volume pumps by filtering 218−561 L of seawater at two to four depth strata (near-surface, ∼300 m, ∼1000 m, and above seafloor), and sediment samples were taken with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
132
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(166 citation statements)
references
References 75 publications
13
132
3
1
Order By: Relevance
“…The prevalence of MP fibres 2,6,7 and polyester 4,6 in our samples is consistent with recent studies of near-surface water in the central Arctic Basin 2 and Hudson Bay and the eastern Canadian Arctic 8 , but contrasts observations of polymer composition in Arctic sea ice and ice floes where varnish (polymer used in coatings) 5,21 , and polyethylene and polypropylene fragments 5 were found to be abundant.…”
Section: Atlanɵc Watersupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of MP fibres 2,6,7 and polyester 4,6 in our samples is consistent with recent studies of near-surface water in the central Arctic Basin 2 and Hudson Bay and the eastern Canadian Arctic 8 , but contrasts observations of polymer composition in Arctic sea ice and ice floes where varnish (polymer used in coatings) 5,21 , and polyethylene and polypropylene fragments 5 were found to be abundant.…”
Section: Atlanɵc Watersupporting
confidence: 91%
“…To account for any artifacts arising from microplastic contamination in our field samples, particles that were visually similar and present across multiple samples were removed from the final analysis. This conservative approach applied in previous research 4 resulted in a large number of particles excluded (a total 60%), but is validated by the similarity of our final estimates to others made for the region 2 . There were no differences among the microplastic contamination values on different cruises and vessels (ANOVA, p > 0.05).…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, bulk water samples from HAUSGARTEN in the Fram Strait contained microplastics (>11 μm) in samples collected from the surface water to just above the seafloor (0-2500 m). Sample volumes ranged from 216 L to 561 L with microplastic concentrations ranging from 0 to 1287 particles per m 3 (Tekman et al 2020). Again, this study supports the transport of microplastic through the water column.…”
Section: Microplastic In Arctic Seawater Samplessupporting
confidence: 73%
“…Mu et al (2019b) found a negative correlation between the microplastic concentration and depth of sample collection in the Chukchi Sea and Strait (range 0-68.73 items per kg dw), whereas concentrations in the Bering Sea and Strait ranged from 5.3 to 39.27 items per kg dw. In the Arctic deepsea observatory, HAUSGARTEN, five sites were investigated at depths from 271 to 5569 m (Tekman et al 2020); microplastic (>11 μm) concentrations were reported ranging from 239 to 13,331 particles per kg. Interestingly, the most commonly identified polymerschlorinated polyethylene (31%)has a density of 0.93-0.96 g/cm 3 which would normally float in seawater, suggesting that these particles sank following biofouling or other biological processes (van Sebille et al 2020).…”
Section: Microplastics In Arctic Sediments and Beachesmentioning
confidence: 99%